Perancangan Antarmuka dan Interaksi Pengguna Website Konfirmasi Kehadiran Acara pada Dinas Komunikasi dan Informatika Kabupaten Kediri menggunakan Metode Design Thinking - Veri Daffa Ramadhani; Buce Trias Hanggara; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Dinas Komunikasi dan Informatika Kabupaten Kediri is one of the local government agencies in the fields of communication and informatics. DISKOMINFO of Kabupaten Kediri is currently planning to develop a web-based service to confirm attendance at an event without using manual paperwork and reduce paper usage for confirm attedance. To solve this problem, a web-based user interface and interaction design is made to simplify the attendance process. The design was created using design thinking method consisting of five steps empathize, define, ideate, prototype, and test. The test was done using usability testing with aspects of effectiveness, efficiency, and satisfaction for civil servant (PNS) and civilian users. The result effectiveness aspect, civil servants scored 90% while the civilian scored 93.3%. The efficiency aspect test shows a result of 0,102 goals/sec and 88,65% for the PNS while 0,150 goals/sec and 94,39% for the civilian. For the satisfaction aspect using the system usability scale, the civil servant scored 79,5, while the civilian scored 79,2. Both of those results can be categorized as